Migracija MAUI aplikacij z uporabo agentov UI - Granda, Alen (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
The official demise of the Xamarin framework places the urgency of transitioning development teams to the modern .NET MAUI platform. For complex organizational applications, standard deterministic tools such as Microsoft Upgrade Assistant are often insufficient. Such systems include advanced architectural patterns, dependencies on external libraries (e.g. DevExpress), and requirements for business logic optimization. The paper analyzes the evolution of migration approaches using artificial intelligence (UI) agents — from local models (Ollama and DeepSeek), which are limited by hardware and context window size, to the cloud-based tool Claude Code. Using a case study of a production application with eight projects and more than 180,000 lines of code, the methodology of dividing the migration into nine logical steps is demonstrated. The results show a 54% time saving. Additionally, the paper highlights typical agent errors and multi-layered security protocols such as the .claudeignore file, which, together with professional code review, enable a safe and optimized implementation of the technology transition.